Dissecting the journey to breast cancer diagnosis in sub‐Saharan Africa: Findings from the multicountry ABC‐DO cohort study. Issue 2 (4th August 2020) - Foerster, Milena; McKenzie, Fiona; Zietsman, Annelle; Galukande, Moses; Anele, Angelica; Adisa, Charles; Parham, Groesbeck; Pinder, Leeya; Schüz, Joachim; McCormack, Valerie; dos‐Santos‐Silva, Isabel
Abstract: Most breast cancer patients in sub‐Saharan Africa are diagnosed at advanced stages after prolonged symptomatic periods. In the multicountry African Breast Cancer‐Disparities in Outcomes cohort, we dissected the diagnostic journey to inform downstaging interventions. At hospital presentation for breast cancer, women recalled their diagnostic journey, including dates of first noticing symptoms and health‐care provider (HCP) visits. Negative binomial regression models were used to identify correlates of the length of the diagnostic journey. Among 1429 women, the median (inter‐quartile range) length (months) of the diagnostic journey ranged from 11.3 (5.7‐21.2) in Ugandan, 8.2 (3.4‐16.4) in Zambian, 6.5 (2.4‐15.7) in Namibian‐black to 5.6 (2.3‐13.1) in Nigerian and 2.4 (0.6‐5.5) in Namibian‐non‐black women. Time from first HCP contact to diagnosis represented, on average, 58% to 79% of the diagnostic journey in each setting except Nigeria where most women presented directly to the diagnostic hospital with advanced disease. The median number of HCPs visited was 1 to 4 per woman, but time intervals between visits were long. Women who attributed their initial symptoms to cancer had a 4.1 months (absolute) reduced diagnostic journey than those who did not, while less‐educated (none/primary) women had a 3.6 months longer journey than more educated women. In most settings the long journey to breast cancer diagnosis was not primarily due to late first presentation but to prolonged delays after first presentation to diagnosis. Promotion of breast cancer awareness and implementation of accelerated referral pathways for women with suspicious symptoms are vital to downstaging the disease in the region. Abstract : What's new? In sub‐Saharan Africa, most women with breast cancer are diagnosed long after symptoms first arise. Here, the authors studied the diagnostic journey for breast cancer among the African Breast Cancer‐Disparities in Outcome cohort. This is the largest study to quantify the length of the diagnostic journey across various settings in sub‐Saharan Africa. Time to final diagnosis decreased substantially when a woman recognized her symptoms as cancer. Most delays, they found, were due to extended time between first examination and final diagnosis. Promotion of breast cancer awareness among both women and healthcare providers could help reduce these delays.